Improved survival of patients with multiple myeloma after the introduction of novel agents and the applicability of the International Staging System (ISS): An analysis of the Greek Myeloma Study Group (GMSG) - Kastritis, E.; Zervas, K.; Symeonidis, A.; Terpos, E.; Delimbassi, S.; Anagnostopoulos, N.; Michali, E.; Zomas, A.; Katodritou, E.; Gika, D.; Pouli, A.; Christoulas, D.; et al. (Leukemia, 2009)
When the novel agents thalidomide, bortezomib and lenalidomide are administered to patients with myeloma in the context of clinical trials, they are associated with a significant improvement in response, progression-free survival and in some studies, overall survival (OS); however, their effect on the outcome of unselected myeloma patients has not been fully assessed. We compared the outcome of 1376 unselected patients with symptomatic myeloma, who started treatment before or after the introduction of thalidomide. The median OS in patients who started treatment after the introduction of novel agents increased by 12 months (48 vs 36 months, P<0.001). This improvement was more pronounced in patients ≤70 years (from 39 to 74 months, P<0.001), but less evident in patients >70 years (from 26 to 33 months, P=0.27). In patients treated after the introduction of novel agents, the international staging system (ISS) could discriminate three groups with significantly different outcomes (5-year survival for ISS stage I, II and III was 66, 45 and 18%, respectively, P<0.001). ISS was also valid in patients who actually received upfront treatment with novel drugs (4-year survival rate was 85, 61 and 26% for ISS stage I, II and III patients, P=0.001).